Super wear-resistant and scratch-resistant UV coating and preparation method thereof

By using foam alumina particles with pigment loaded in UV coatings and modified polyurethane acrylic resin, the problems of poor wear resistance and uneven color are solved, and higher wear resistance and color uniformity are achieved.

CN119552572AActive Publication Date: 2025-03-04DONGZHOU CHEM IND (KUNSHAN) CO LTD
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202411599884.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-11
Publication Date
2025-03-04
Estimated Expiration
2044-11-11

AI Technical Summary

Technical Problem

The existing UV coatings have poor wear resistance and uneven color, making it difficult to meet the higher requirements of modern industry for material performance.

Method used

By adding foam alumina particles loaded with pigments to the coating, the porous structure is used to adsorb the pigment, forming a micro-nano structure, improving the tribological properties of the coating, and enhancing the density and wear resistance of the coating by modifying polyurethane acrylic resin and other additives.

Benefits of technology

It significantly improves the wear resistance and color uniformity of the coating, reduces friction and wear, enhances the friction and drag reduction performance of the coating, and improves the stability and wear color fastness of the pigment.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005127988290000011
    Figure BDA0005127988290000011
  • Figure BDA0005127988290000121
    Figure BDA0005127988290000121
  • Figure BDA0005127988290000131
    Figure BDA0005127988290000131
Patent Text Reader

Abstract

The invention provides a super wear-resistant and scratch-resistant UV coating. The super wear-resistant and scratch-resistant UV coating is prepared from the following components in parts by weight: 100-150 parts of modified polyurethane acrylic resin, 20-40 parts of a reactive diluent, 4-6 parts of a photoinitiator, 3-10 parts of pigment-loaded foamed aluminum oxide particles, 3-10 parts of a BYK331 leveling agent and 0.5-2 parts of an auxiliary agent, the particle size of the foamed aluminum oxide particles loaded with the pigment is 10-100 microns, and the porosity of the foamed aluminum oxide is 80-97%. According to the super wear-resistant and scratch-resistant UV coating and the preparation method thereof provided by the invention, a micro-nano structure is formed on the surface of a coating through a micro-structure of foamed aluminum oxide particles, a nano-structure of pigment and micro (nano)-meter holes of the foamed aluminum oxide particles, so that the tribological performance of the coating is improved, friction and wear are reduced, and the anti-friction and anti-drag performance of the coating is improved; foamed aluminum oxide is of a porous structure, has rich pore structures, can adsorb a large amount of pigment, enables the pigment to be uniformly dispersed, and avoids agglomeration caused by direct addition of the foamed aluminum oxide into the coating and nonuniform color of the coating.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field The invention relates to the field of coatings, and in particular to a super wear-resistant and scratch-resistant UV coating and a preparation method thereof. Background Art Ultraviolet (UV) curing coating and its coating technology are new surface treatment technologies that emerged in the 1980s. This type of coating uses ultraviolet radiation to initiate resin curing. Compared with existing thermosetting coatings, it has the advantages of fast curing, energy saving, room temperature curing, less pollution, and superior coating performance. It is a new generation of green chemical products. However, with the continuous improvement of modern industry's requirements for material performance, although UV curing coatings have relatively good wear resistance, various industries have further requirements for their wear resistance and scratch resistance. Therefore, the development of new ultra-wear-resistant and scratch-resistant coatings has become a research hotspot in the fields of materials science and surface engineering. These coatings usually achieve their excellent performance by introducing specific nanoparticles, using advanced coating preparation technologies (such as physical vapor deposition, chemical vapor deposition, thermal spraying, etc.) and optimizing the microstructure of the coating. However, direct addition of nanoparticles is prone to agglomeration, especially when the pigment is also nano-type, the pigment is also easy to agglomerate, resulting in uneven color, and the pigment cannot be protected and is easy to fade during wear. The above problems need to be solved urgently. Summary of the invention

[0003] Technical problem to be solved: In view of the technical problems of poor wear resistance and uneven color of current UV coatings, the present invention proposes a super wear-resistant and scratch-resistant UV coating and a preparation method thereof. A micron-structure is formed on the coating surface through the micron structure of foamed alumina particles, the nanostructure of pigments and the micro (nano) pores of foamed alumina particles, thereby improving the tribological properties of the coating, reducing friction and wear, and improving the friction and drag reduction properties of the coating. The foamed alumina has a porous structure with rich pore structure, can absorb a large amount of pigments, make the pigments evenly dispersed, and avoid agglomeration caused by direct addition to the coating, which makes the coating color uneven. The present invention.

[0004] Technical solution: A super wear-resistant and scratch-resistant UV coating, comprising the following components in parts by weight: The particle size of the pigment-loaded foamed alumina particles is 10-100 μm, and the porosity of the foamed alumina particles is 80-97%. Furthermore, the preparation method of the modified polyurethane acrylic resin is as follows, in parts by weight: (1) 5 parts of hydroxy-terminated polydimethylsiloxane, 4.5 parts of pentaerythritol triacrylate, 0.1 parts of dibutyltin dilaurate and 0.2 parts of p-hydroxyanisole were mixed, N2 was introduced, and the mixture was stirred uniformly; (2) Raise the temperature to 80°C and begin to dropwise add 100 parts of isophorone diisocyanate for 3-4 hours; (3) Pentaerythritol triacrylate is added to neutralize the unreacted isocyanate groups to obtain modified polyurethane acrylic resin. Furthermore, the active diluent is a complex of HDDA and DPHA in a ratio of 1:(1-1.5). Furthermore, the photoinitiator is a mixture of benzophenone and hydroxycyclohexyl phenyl ketone, or one or more mixtures of acylphosphorus oxides. Furthermore, the preparation method of the pigment-loaded foamed alumina particles is as follows: Step 1: soak a polyurethane foam with a pore size of 100 PPI in a 10-20% NaOH solution for 2-3 hours, then soak it in a constant temperature water bath at 60°C for 3 hours, rub it repeatedly to remove the inter-grid membrane, and rinse it with water to obtain the treated polyurethane foam; Step 2: Take 50-80 parts of nano-alumina, 5-8 parts of mesoporous alumina fibers, 3-6 parts of hollow silicon carbide microspheres, 3-5 parts of magnesium oxide, 10-15 parts of silicon powder and 2-5 parts of nano-zirconium oxide, mix and stir evenly to obtain a mixed component, add a 35-50% aluminum dihydrogen phosphate solution to form a slurry, and slurry for 12 hours; Step 3: placing the treated polyurethane foam in the slurry, repeatedly dipping and squeezing, removing the air in the polyurethane foam, and when the slurry is fully immersed in the polyurethane foam and uniformly adsorbed on the polyurethane foam, squeezing the saturated polyurethane foam, squeezing out the excess slurry, and obtaining the green blank; Step 4: After drying the green blank at 80°C, transfer it to a high-temperature box-type resistance furnace for sintering, heat it to 600°C at a heating rate of 0.5°C / min, keep it warm for 2 hours, continue to heat it to 1200°C at a heating rate of 0.3°C / min, keep it warm for 10 hours, and obtain foamed alumina; Step 5: clean the foamed alumina, dry it, crush it and sieve it to obtain foamed alumina particles; Step 6: Take 6 parts of foamed alumina particles, add 100 parts of water, add citric acid to modify, then add 2 parts of organic pigments, and keep the temperature at 70°C for 1-2 hours; Step 7: Add 6 parts of silane coupling agent and 20 parts of 95% ethanol, and react at 70°C for 1-2 hours; Step 8: Add 1.2-1.5 parts of methyl methacrylate, 20 parts of 95% ethanol and ammonium persulfate, and react for 2-3 hours; Step 9: After filtering, dry in the air, wash with 95% ethanol, and dry to obtain the pigment-loaded foamed alumina particles. Furthermore, the particle size of the nano-alumina is 30-100nm, the particle size of the hollow silicon carbide microspheres is 400-580nm, the particle size of the magnesium oxide is 260-500nm, the particle size of the silicon micropowder is 0.5-2μm, and the particle size of the nano-zirconia is 30-80nm. Furthermore, the surface of the mesoporous alumina fiber has mesopores of 2-4 nm and an average specific surface area of ​​322 m 2 / g, fiber diameter is 200-300nm, and length is 7-10μm. Furthermore, the mass of the aluminum dihydrogen phosphate solution is 20-25% of the mixed components. Furthermore, the auxiliary agent is any one of a defoaming agent, a formaldehyde removal additive, and an antibacterial additive, or a combination of two or more thereof. The preparation method of the above-mentioned ultra-wear-resistant and scratch-resistant UV coating comprises the following steps: after uniformly mixing the modified polyurethane acrylic resin, active diluent, photoinitiator, BYK331 leveling agent and additives, adding the pigment-loaded foamed alumina particles, and stirring evenly again. Beneficial effects: 1. In the present invention, foamed alumina particles loaded with pigments are added to the coating. The foamed alumina has a porous structure and rich pore structure, and can absorb a large amount of pigments to make the pigments evenly dispersed, thereby avoiding agglomeration caused by direct addition to the coating, which makes the coating color uneven. 2. The present invention forms a micro-nano structure on the coating surface through the micron structure of foamed alumina particles, the nanostructure of the pigment and the micro (nano) pores of the foamed alumina particles, thereby improving the tribological properties of the coating, reducing friction and wear, and improving the friction and drag reduction performance of the coating. 3. The present invention adds mesoporous alumina fibers in the preparation of foamed alumina particles. The mesopores can further increase the pore structure and enhance the adsorption of pigments. At the same time, the two-dimensional structure of the alumina fibers can form a "skeleton" in the foamed alumina structure, bearing most of the load, reducing stress concentration, facilitating load transfer and dispersing cracks, preventing or slowing down the propagation of cracks, and increasing the toughness and wear resistance of the foamed alumina particles. 4. The present invention adds hollow silicon carbide microspheres in the preparation of foamed alumina particles. The hollow silicon carbide microspheres have high strength and a modulus higher than that of nano-alumina, which can increase the toughness of the foamed alumina particles and significantly improve their strength. 5. The present invention can improve the stability, dispersibility and abrasion-resistant color fastness of the pigment by adsorbing the pigment into the pores and surface of the foamed aluminum oxide particles and fixing them with polymethyl methacrylate. 6. The present invention modifies the polyurethane acrylic resin and introduces silanol groups and hydroxyl groups on the surface of the polyurethane acrylic resin, which can form a stable spatial network structure with the foamed alumina particles loaded with pigments, thereby enhancing the density and wear resistance of the coating. DETAILED DESCRIPTION Example 1 The preparation method of the pigment-loaded foamed alumina particles is as follows: Step 1: soak a polyurethane foam with a pore size of 100 PPI in a 20% NaOH solution for 2 hours, then soak it in a constant temperature water bath at 60°C for 3 hours, rub it repeatedly to remove the inter-grid membrane, and rinse it with water to obtain the treated polyurethane foam; Step 2: Take 80 parts of nano-alumina with a particle size of 30-100 nm, 5 parts of mesoporous alumina fiber (the surface of the mesoporous alumina fiber has 2-4 nm mesopores and an average specific surface area of ​​322 m 2 / g, fiber diameter of 200-300nm, length of 7-10μm), 5 parts of silicon carbide hollow microspheres with a particle size of 400-580nm, 4 parts of magnesium oxide with a particle size of 260-500nm, 15 parts of silicon micropowder with a particle size of 0.5-2μm and 5 parts of nano zirconium oxide with a particle size of 30-80nm, mix and stir evenly to obtain a mixed component, add a 40% aluminum dihydrogen phosphate solution, the mass of the aluminum dihydrogen phosphate solution is 25% of the mixed component, form a slurry, and trap the slurry for 12h; Step 3: placing the treated polyurethane foam in the slurry, repeatedly dipping and squeezing, removing the air in the polyurethane foam, and when the slurry is fully immersed in the polyurethane foam and uniformly adsorbed on the polyurethane foam, squeezing the saturated polyurethane foam, squeezing out the excess slurry, and obtaining the green blank; Step 4: After drying the green blank at 80°C, transfer it to a high-temperature box-type resistance furnace for sintering, heat it to 600°C at a heating rate of 0.5°C / min, keep it warm for 2 hours, continue to heat it to 1200°C at a heating rate of 0.3°C / min, keep it warm for 10 hours, and obtain foamed alumina; Step 5: clean the foamed alumina, dry it, crush it and sieve it to obtain foamed alumina particles; Step 6: Take 6 parts of foamed alumina particles, add 100 parts of water, add citric acid to modify, then add 2 parts of organic pigments, and keep the temperature at 70°C for 1-2 hours; Step 7: Add 6 parts of silane coupling agent and 20 parts of 95% ethanol, and react at 70°C for 2h; Step 8: Add 1.4 parts of methyl methacrylate, 20 parts of 95% ethanol and ammonium persulfate, and react for 3 hours; Step 9: After filtering, air-drying, washing with 95% ethanol, and drying to obtain pigment-loaded foamed alumina particles with a particle size of 10-100 μm. Example 2 The preparation method of the pigment-loaded foamed alumina particles is as follows: Step 1: soak a polyurethane foam with a pore size of 100 PPI in a 20% NaOH solution for 2 hours, then soak it in a constant temperature water bath at 60°C for 3 hours, rub it repeatedly to remove the inter-grid membrane, and rinse it with water to obtain the treated polyurethane foam; Step 2: Take 80 parts of nano-alumina with a particle size of 30-100 nm, 7 parts of mesoporous alumina fiber (the surface of the mesoporous alumina fiber has 2-4 nm mesopores and an average specific surface area of ​​322 m 2 / g, fiber diameter of 200-300nm, length of 7-10μm), 5 parts of silicon carbide hollow microspheres with a particle size of 400-580nm, 4 parts of magnesium oxide with a particle size of 260-500nm, 15 parts of silicon micropowder with a particle size of 0.5-2μm and 5 parts of nano zirconium oxide with a particle size of 30-80nm, mix and stir evenly to obtain a mixed component, add a 40% aluminum dihydrogen phosphate solution, the mass of the aluminum dihydrogen phosphate solution is 25% of the mixed component, form a slurry, and trap the slurry for 12h; Step 3: placing the treated polyurethane foam in the slurry, repeatedly dipping and squeezing, removing the air in the polyurethane foam, and when the slurry is fully immersed in the polyurethane foam and uniformly adsorbed on the polyurethane foam, squeezing the saturated polyurethane foam, squeezing out the excess slurry, and obtaining the green blank; Step 4: After drying the green blank at 80°C, transfer it to a high-temperature box-type resistance furnace for sintering, heat it to 600°C at a heating rate of 0.5°C / min, keep it warm for 2 hours, continue to heat it to 1200°C at a heating rate of 0.3°C / min, keep it warm for 10 hours, and obtain foamed alumina; Step 5: clean the foamed alumina, dry it, crush it and sieve it to obtain foamed alumina particles; Step 6: Take 6 parts of foamed alumina particles, add 100 parts of water, add citric acid to modify, then add 2 parts of organic pigments, and keep the temperature at 70°C for 1-2 hours; Step 7: Add 6 parts of silane coupling agent and 20 parts of 95% ethanol, and react at 70°C for 2h; Step 8: Add 1.4 parts of methyl methacrylate, 20 parts of 95% ethanol and ammonium persulfate, and react for 3 hours; Step 9: After filtering, air-drying, washing with 95% ethanol, and drying to obtain pigment-loaded foamed alumina particles with a particle size of 10-100 μm. Example 3 The preparation method of the pigment-loaded foamed alumina particles is as follows: Step 1: soak a polyurethane foam with a pore size of 100 PPI in a 20% NaOH solution for 2 hours, then soak it in a constant temperature water bath at 60°C for 3 hours, rub it repeatedly to remove the inter-grid membrane, and rinse it with water to obtain the treated polyurethane foam; Step 2: Take 80 parts of nano-alumina with a particle size of 30-100 nm, 8 parts of mesoporous alumina fiber (the surface of the mesoporous alumina fiber has 2-4 nm mesopores and an average specific surface area of ​​322 m 2 / g, fiber diameter of 200-300nm, length of 7-10μm), 5 parts of silicon carbide hollow microspheres with a particle size of 400-580nm, 4 parts of magnesium oxide with a particle size of 260-500nm, 15 parts of silicon micropowder with a particle size of 0.5-2μm and 5 parts of nano zirconium oxide with a particle size of 30-80nm, mix and stir evenly to obtain a mixed component, add a 40% aluminum dihydrogen phosphate solution, the mass of the aluminum dihydrogen phosphate solution is 25% of the mixed component, form a slurry, and trap the slurry for 12h; Step 3: placing the treated polyurethane foam in the slurry, repeatedly dipping and squeezing, removing the air in the polyurethane foam, and when the slurry is fully immersed in the polyurethane foam and uniformly adsorbed on the polyurethane foam, squeezing the saturated polyurethane foam, squeezing out the excess slurry, and obtaining the green blank; Step 4: After drying the green blank at 80°C, transfer it to a high-temperature box-type resistance furnace for sintering, heat it to 600°C at a heating rate of 0.5°C / min, keep it warm for 2 hours, continue to heat it to 1200°C at a heating rate of 0.3°C / min, keep it warm for 10 hours, and obtain foamed alumina; Step 5: clean the foamed alumina, dry it, crush it and sieve it to obtain foamed alumina particles; Step 6: Take 6 parts of foamed alumina particles, add 100 parts of water, add citric acid to modify, then add 2 parts of organic pigments, and keep the temperature at 70°C for 1-2 hours; Step 7: Add 6 parts of silane coupling agent and 20 parts of 95% ethanol, and react at 70°C for 2h; Step 8: Add 1.4 parts of methyl methacrylate, 20 parts of 95% ethanol and ammonium persulfate, and react for 3 hours; Step 9: After filtering, air-drying, washing with 95% ethanol, and drying to obtain pigment-loaded foamed alumina particles with a particle size of 10-100 μm. Example 4 The preparation method of the pigment-loaded foamed alumina particles is as follows: Step 1: soak a polyurethane foam with a pore size of 100 PPI in a 20% NaOH solution for 2 hours, then soak it in a constant temperature water bath at 60°C for 3 hours, rub it repeatedly to remove the inter-grid membrane, and rinse it with water to obtain the treated polyurethane foam; Step 2: Take 80 parts of nano-alumina with a particle size of 30-100 nm, 7 parts of mesoporous alumina fiber (the surface of the mesoporous alumina fiber has 2-4 nm mesopores and an average specific surface area of ​​322 m 2 / g, fiber diameter of 200-300nm, length of 7-10μm), 3 parts of silicon carbide hollow microspheres with a particle size of 400-580nm, 4 parts of magnesium oxide with a particle size of 260-500nm, 15 parts of silicon micropowder with a particle size of 0.5-2μm and 5 parts of nano zirconium oxide with a particle size of 30-80nm, mix and stir evenly to obtain a mixed component, add a 40% aluminum dihydrogen phosphate solution, the mass of the aluminum dihydrogen phosphate solution is 25% of the mixed component, form a slurry, and trap the slurry for 12h; Step 3: placing the treated polyurethane foam in the slurry, repeatedly dipping and squeezing, removing the air in the polyurethane foam, and when the slurry is fully immersed in the polyurethane foam and uniformly adsorbed on the polyurethane foam, squeezing the saturated polyurethane foam, squeezing out the excess slurry, and obtaining the green blank; Step 4: After drying the green blank at 80°C, transfer it to a high-temperature box-type resistance furnace for sintering, heat it to 600°C at a heating rate of 0.5°C / min, keep it warm for 2 hours, continue to heat it to 1200°C at a heating rate of 0.3°C / min, keep it warm for 10 hours, and obtain foamed alumina; Step 5: clean the foamed alumina, dry it, crush it and sieve it to obtain foamed alumina particles; Step 6: Take 6 parts of foamed alumina particles, add 100 parts of water, add citric acid to modify, then add 2 parts of organic pigments, and keep the temperature at 70°C for 1-2 hours; Step 7: Add 6 parts of silane coupling agent and 20 parts of 95% ethanol, and react at 70°C for 2h; Step 8: Add 1.4 parts of methyl methacrylate, 20 parts of 95% ethanol and ammonium persulfate, and react for 3 hours; Step 9: After filtering, air-drying, washing with 95% ethanol, and drying to obtain pigment-loaded foamed alumina particles with a particle size of 10-100 μm. Example 5 The preparation method of the pigment-loaded foamed alumina particles is as follows: Step 1: soak a polyurethane foam with a pore size of 100 PPI in a 20% NaOH solution for 2 hours, then soak it in a constant temperature water bath at 60°C for 3 hours, rub it repeatedly to remove the inter-grid membrane, and rinse it with water to obtain the treated polyurethane foam; Step 2: Take 80 parts of nano-alumina with a particle size of 30-100 nm, 7 parts of mesoporous alumina fiber (the surface of the mesoporous alumina fiber has 2-4 nm mesopores and an average specific surface area of ​​322 m 2 / g, fiber diameter of 200-300nm, length of 7-10μm), 6 parts of silicon carbide hollow microspheres with a particle size of 400-580nm, 4 parts of magnesium oxide with a particle size of 260-500nm, 15 parts of silicon micropowder with a particle size of 0.5-2μm and 5 parts of nano zirconium oxide with a particle size of 30-80nm, mix and stir evenly to obtain a mixed component, add a 40% aluminum dihydrogen phosphate solution, the mass of the aluminum dihydrogen phosphate solution is 25% of the mixed component, form a slurry, and trap the slurry for 12h; Step 3: placing the treated polyurethane foam in the slurry, repeatedly dipping and squeezing, removing the air in the polyurethane foam, and when the slurry is fully immersed in the polyurethane foam and uniformly adsorbed on the polyurethane foam, squeezing the saturated polyurethane foam, squeezing out the excess slurry, and obtaining the green blank; Step 4: After drying the green blank at 80°C, transfer it to a high-temperature box-type resistance furnace for sintering, heat it to 600°C at a heating rate of 0.5°C / min, keep it warm for 2 hours, continue to heat it to 1200°C at a heating rate of 0.3°C / min, keep it warm for 10 hours, and obtain foamed alumina; Step 5: clean the foamed alumina, dry it, crush it and sieve it to obtain foamed alumina particles; Step 6: Take 6 parts of foamed alumina particles, add 100 parts of water, add citric acid to modify, then add 2 parts of organic pigments, and keep the temperature at 70°C for 1-2 hours; Step 7: Add 6 parts of silane coupling agent and 20 parts of 95% ethanol, and react at 70°C for 2h; Step 8: Add 1.4 parts of methyl methacrylate, 20 parts of 95% ethanol and ammonium persulfate, and react for 3 hours; Step 9: After filtering, air-drying, washing with 95% ethanol, and drying to obtain pigment-loaded foamed alumina particles with a particle size of 10-100 μm. Example 6 The preparation method of the pigment-loaded foamed alumina particles is as follows: Step 1: soak a polyurethane foam with a pore size of 100 PPI in a 20% NaOH solution for 2 hours, then soak it in a constant temperature water bath at 60°C for 3 hours, rub it repeatedly to remove the inter-grid membrane, and rinse it with water to obtain the treated polyurethane foam; Step 2: Take 80 parts of nano-alumina with a particle size of 30-100 nm, 7 parts of mesoporous alumina fiber (the surface of the mesoporous alumina fiber has 2-4 nm mesopores and an average specific surface area of ​​322 m 2 / g, fiber diameter of 200-300nm, length of 7-10μm), 5 parts of silicon carbide hollow microspheres with a particle size of 400-580nm, 4 parts of magnesium oxide with a particle size of 260-500nm, 15 parts of silicon micropowder with a particle size of 0.5-2μm and 5 parts of nano zirconium oxide with a particle size of 30-80nm, mix and stir evenly to obtain a mixed component, add a 40% aluminum dihydrogen phosphate solution, the mass of the aluminum dihydrogen phosphate solution is 25% of the mixed component, form a slurry, and trap the slurry for 12h; Step 3: placing the treated polyurethane foam in the slurry, repeatedly dipping and squeezing, removing the air in the polyurethane foam, and when the slurry is fully immersed in the polyurethane foam and uniformly adsorbed on the polyurethane foam, squeezing the saturated polyurethane foam, squeezing out the excess slurry, and obtaining the green blank; Step 4: After drying the green blank at 80°C, transfer it to a high-temperature box-type resistance furnace for sintering, heat it to 600°C at a heating rate of 0.5°C / min, keep it warm for 2 hours, continue to heat it to 1200°C at a heating rate of 0.3°C / min, keep it warm for 10 hours, and obtain foamed alumina; Step 5: clean the foamed alumina, dry it, crush it and sieve it to obtain foamed alumina particles; Step 6: Take 6 parts of foamed alumina particles, add 100 parts of water, add citric acid to modify, then add 2 parts of organic pigments, and keep the temperature at 70°C for 1-2 hours; Step 7: Add 6 parts of silane coupling agent and 20 parts of 95% ethanol, and react at 70°C for 2h; Step 8: Add 1.2 parts of methyl methacrylate, 20 parts of 95% ethanol and ammonium persulfate, and react for 3 hours; Step 9: After filtering, air-drying, washing with 95% ethanol, and drying to obtain pigment-loaded foamed alumina particles with a particle size of 10-100 μm. Example 7 The preparation method of the pigment-loaded foamed alumina particles is as follows: Step 1: soak a polyurethane foam with a pore size of 100 PPI in a 20% NaOH solution for 2 hours, then soak it in a constant temperature water bath at 60°C for 3 hours, rub it repeatedly to remove the inter-grid membrane, and rinse it with water to obtain the treated polyurethane foam; Step 2: Take 80 parts of nano-alumina with a particle size of 30-100 nm, 7 parts of mesoporous alumina fiber (the surface of the mesoporous alumina fiber has 2-4 nm mesopores and an average specific surface area of ​​322 m 2 / g, fiber diameter of 200-300nm, length of 7-10μm), 5 parts of silicon carbide hollow microspheres with a particle size of 400-580nm, 4 parts of magnesium oxide with a particle size of 260-500nm, 15 parts of silicon micropowder with a particle size of 0.5-2μm and 5 parts of nano zirconium oxide with a particle size of 30-80nm, mix and stir evenly to obtain a mixed component, add a 40% aluminum dihydrogen phosphate solution, the mass of the aluminum dihydrogen phosphate solution is 25% of the mixed component, form a slurry, and trap the slurry for 12h; Step 3: placing the treated polyurethane foam in the slurry, repeatedly dipping and squeezing, removing the air in the polyurethane foam, and when the slurry is fully immersed in the polyurethane foam and uniformly adsorbed on the polyurethane foam, squeezing the saturated polyurethane foam, squeezing out the excess slurry, and obtaining the green blank; Step 4: After drying the green blank at 80°C, transfer it to a high-temperature box-type resistance furnace for sintering, heat it to 600°C at a heating rate of 0.5°C / min, keep it warm for 2 hours, continue to heat it to 1200°C at a heating rate of 0.3°C / min, keep it warm for 10 hours, and obtain foamed alumina; Step 5: clean the foamed alumina, dry it, crush it and sieve it to obtain foamed alumina particles; Step 6: Take 6 parts of foamed alumina particles, add 100 parts of water, add citric acid to modify, then add 2 parts of organic pigments, and keep the temperature at 70°C for 1-2 hours; Step 7: Add 6 parts of silane coupling agent and 20 parts of 95% ethanol, and react at 70°C for 2h; Step 8: Add 1.5 parts of methyl methacrylate, 20 parts of 95% ethanol and ammonium persulfate, and react for 3 hours; Step 9: After filtering, air-drying, washing with 95% ethanol, and drying to obtain pigment-loaded foamed alumina particles with a particle size of 10-100 μm. Comparative Example 1 The difference between this embodiment and embodiment 2 is that mesoporous alumina fiber is not used, but nano alumina is used instead, as follows: The preparation method of the pigment-loaded foamed alumina particles is as follows: Step 1: soak a polyurethane foam with a pore size of 100 PPI in a 20% NaOH solution for 2 hours, then soak it in a constant temperature water bath at 60°C for 3 hours, rub it repeatedly to remove the inter-grid membrane, and rinse it with water to obtain the treated polyurethane foam; Step 2: Take 87 parts of nano-alumina with a particle size of 30-100nm, 5 parts of hollow silicon carbide microspheres with a particle size of 400-580nm, 4 parts of magnesium oxide with a particle size of 260-500nm, 15 parts of silicon micropowder with a particle size of 0.5-2μm and 5 parts of nano-zirconium oxide with a particle size of 30-80nm, mix and stir evenly to obtain a mixed component, add a 40% aluminum dihydrogen phosphate solution, the mass of the aluminum dihydrogen phosphate solution is 25% of the mixed component, form a slurry, and slurry is trapped for 12h; Step 3: placing the treated polyurethane foam in the slurry, repeatedly dipping and squeezing, removing the air in the polyurethane foam, and when the slurry is fully immersed in the polyurethane foam and uniformly adsorbed on the polyurethane foam, squeezing the saturated polyurethane foam, squeezing out the excess slurry, and obtaining the green blank; Step 4: After drying the green blank at 80°C, transfer it to a high-temperature box-type resistance furnace for sintering, heat it to 600°C at a heating rate of 0.5°C / min, keep it warm for 2 hours, continue to heat it to 1200°C at a heating rate of 0.3°C / min, keep it warm for 10 hours, and obtain foamed alumina; Step 5: clean the foamed alumina, dry it, crush it and sieve it to obtain foamed alumina particles; Step 6: Take 6 parts of foamed alumina particles, add 100 parts of water, add citric acid to modify, then add 2 parts of organic pigments, and keep the temperature at 70°C for 1-2 hours; Step 7: Add 6 parts of silane coupling agent and 20 parts of 95% ethanol, and react at 70°C for 2h; Step 8: Add 1.4 parts of methyl methacrylate, 20 parts of 95% ethanol and ammonium persulfate, and react for 3 hours; Step 9: After filtering, air-drying, washing with 95% ethanol, and drying to obtain pigment-loaded foamed alumina particles with a particle size of 10-100 μm. Comparative Example 2 The difference between this embodiment and embodiment 2 is that silicon carbide hollow microspheres are not used, but nano-alumina is used instead, as follows: The preparation method of the pigment-loaded foamed alumina particles is as follows: Step 1: soak a polyurethane foam with a pore size of 100 PPI in a 20% NaOH solution for 2 hours, then soak it in a constant temperature water bath at 60°C for 3 hours, rub it repeatedly to remove the inter-grid membrane, and rinse it with water to obtain the treated polyurethane foam; Step 2: Take 85 parts of nano-alumina with a particle size of 30-100 nm, 7 parts of mesoporous alumina fiber (the surface of the mesoporous alumina fiber has 2-4 nm mesopores and an average specific surface area of ​​322 m 2 / g, fiber diameter of 200-300nm, length of 7-10μm), 4 parts of magnesium oxide with a particle size of 260-500nm, 15 parts of silicon powder with a particle size of 0.5-2μm and 5 parts of nano zirconium oxide with a particle size of 30-80nm, mix and stir evenly to obtain a mixed component, add a 40% aluminum dihydrogen phosphate solution, the mass of the aluminum dihydrogen phosphate solution is 25% of the mixed component, form a slurry, and trap the slurry for 12h; Step 3: placing the treated polyurethane foam in the slurry, repeatedly dipping and squeezing, removing the air in the polyurethane foam, and when the slurry is fully immersed in the polyurethane foam and uniformly adsorbed on the polyurethane foam, squeezing the saturated polyurethane foam, squeezing out the excess slurry, and obtaining the green blank; Step 4: After drying the green blank at 80°C, transfer it to a high-temperature box-type resistance furnace for sintering, heat it to 600°C at a heating rate of 0.5°C / min, keep it warm for 2 hours, continue to heat it to 1200°C at a heating rate of 0.3°C / min, keep it warm for 10 hours, and obtain foamed alumina; Step 5: clean the foamed alumina, dry it, crush it and sieve it to obtain foamed alumina particles; Step 6: Take 6 parts of foamed alumina particles, add 100 parts of water, add citric acid to modify, then add 2 parts of organic pigments, and keep the temperature at 70°C for 1-2 hours; Step 7: Add 6 parts of silane coupling agent and 20 parts of 95% ethanol, and react at 70°C for 2h; Step 8: Add 1.4 parts of methyl methacrylate, 20 parts of 95% ethanol and ammonium persulfate, and react for 3 hours; Step 9: After filtering, air-drying, washing with 95% ethanol, and drying to obtain pigment-loaded foamed alumina particles with a particle size of 10-100 μm. Comparative Example 3 The difference between this embodiment and embodiment 2 is that methyl methacrylate is not used to form the shell layer, specifically as follows: The preparation method of the pigment-loaded foamed alumina particles is as follows: Step 1: soak a polyurethane foam with a pore size of 100 PPI in a 20% NaOH solution for 2 hours, then soak it in a constant temperature water bath at 60°C for 3 hours, rub it repeatedly to remove the inter-grid membrane, and rinse it with water to obtain the treated polyurethane foam; Step 2: Take 80 parts of nano-alumina with a particle size of 30-100 nm, 7 parts of mesoporous alumina fiber (the surface of the mesoporous alumina fiber has 2-4 nm mesopores and an average specific surface area of ​​322 m 2 / g, fiber diameter of 200-300nm, length of 7-10μm), 5 parts of silicon carbide hollow microspheres with a particle size of 400-580nm, 4 parts of magnesium oxide with a particle size of 260-500nm, 15 parts of silicon micropowder with a particle size of 0.5-2μm and 5 parts of nano zirconium oxide with a particle size of 30-80nm, mix and stir evenly to obtain a mixed component, add a 40% aluminum dihydrogen phosphate solution, the mass of the aluminum dihydrogen phosphate solution is 25% of the mixed component, form a slurry, and trap the slurry for 12h; Step 3: placing the treated polyurethane foam in the slurry, repeatedly dipping and squeezing, removing the air in the polyurethane foam, and when the slurry is fully immersed in the polyurethane foam and uniformly adsorbed on the polyurethane foam, squeezing the saturated polyurethane foam, squeezing out the excess slurry, and obtaining the green blank; Step 4: After drying the green blank at 80°C, transfer it to a high-temperature box-type resistance furnace for sintering, heat it to 600°C at a heating rate of 0.5°C / min, keep it warm for 2 hours, continue to heat it to 1200°C at a heating rate of 0.3°C / min, keep it warm for 10 hours, and obtain foamed alumina; Step 5: clean the foamed alumina, dry it, crush it and sieve it to obtain foamed alumina particles; Step 6: Take 6 parts of foamed alumina particles, add 100 parts of water, add citric acid for modification, then add 2 parts of organic pigments, keep constant temperature at 70°C for 1-2 hours, filter and dry to obtain foamed alumina particles loaded with pigments with a particle size of 10-100μm. The porosity, pigment loading rate, color fixation rate and compressive strength of the pigment-loaded foamed alumina particles prepared in the above examples were measured: Determination of color fixation rate: 1.000 g of pigment-loaded foamed alumina particles was added with 95% ethanol, placed in a 25°C constant temperature biological shaker for 7 days, filtered, and the absorbance of the filtrate was measured with a spectrophotometer. The concentration was calculated based on the absorbance, and the color fixation rate (%) was calculated based on the concentration difference; The results are shown in Table 1 below: Table 1 Porosity (%) Pigment loading rate (%) Fixation rate (%) Compressive strength(MPa) Example 1 86.3 91.7 97.3 13.3 Example 2 85.8 92.2 97.4 13.8 Example 3 85.5 92.4 97.3 13.9 Example 4 87.1 92.5 97.3 13.5 Example 5 86.2 92.0 97.4 13.9 Example 6 86.8 92.2 95.8 13.7 Example 7 86.1 92.2 97.4 13.8 Comparative Example 1 87.0 88.3 97.1 10.4 Comparative Example 2 87.8 92.6 97.3 11.9 Comparative Example 3 87.0 92.2 82.7 13.7 By comprehensively comparing the various properties of the above-mentioned pigment-loaded foamed alumina particles, Example 2 was selected for subsequent experiments. Example 8 The preparation method of the modified polyurethane acrylic resin is as follows, in parts by weight: (1) 5 parts of hydroxy-terminated polydimethylsiloxane, 4.5 parts of pentaerythritol triacrylate, 0.1 parts of dibutyltin dilaurate and 0.2 parts of p-hydroxyanisole were mixed, N2 was introduced, and the mixture was stirred uniformly; (2) Raise the temperature to 80°C and begin to dropwise add 100 parts of isophorone diisocyanate and react for 4 hours; (3) Pentaerythritol triacrylate is added to neutralize the unreacted isocyanate groups to obtain modified polyurethane acrylic resin. Example 9 A method for preparing a super wear-resistant and scratch-resistant UV coating comprises the following steps: evenly mixing 150 parts of modified polyurethane acrylic resin, 15 parts of HDDA, 15 parts of DPHA, 6 parts of a mixture of benzophenone and hydroxycyclohexyl phenyl ketone, 8 parts of BYK331 leveling agent and 0.5 parts of chitosan, adding 3 parts of foamed alumina particles loaded with pigments, and stirring evenly again. Example 10 A method for preparing a super wear-resistant and scratch-resistant UV coating comprises the following steps: evenly mixing 150 parts of modified polyurethane acrylic resin, 15 parts of HDDA, 15 parts of DPHA, 6 parts of a mixture of benzophenone and hydroxycyclohexyl phenyl ketone, 8 parts of BYK331 leveling agent and 0.5 parts of chitosan, adding 7 parts of pigment-loaded foamed alumina particles, and stirring evenly again. Embodiment 11 A method for preparing a super wear-resistant and scratch-resistant UV coating comprises the following steps: evenly mixing 150 parts of modified polyurethane acrylic resin, 15 parts of HDDA, 15 parts of DPHA, 6 parts of a mixture of benzophenone and hydroxycyclohexyl phenyl ketone, 8 parts of BYK331 leveling agent and 0.5 parts of chitosan, adding 10 parts of pigment-loaded foamed alumina particles, and stirring evenly again. Comparative Example 4 The difference between this example and Example 10 is that the pigment-loaded foamed alumina particles of Comparative Example 1 were used. Comparative Example 5 The difference between this example and Example 10 is that the pigment-loaded foamed alumina particles of Comparative Example 2 were used. Comparative Example 6 The difference between this example and Example 10 is that the pigment-loaded foamed alumina particles of Comparative Example 3 were used. Comparative Example 7 The difference between this example and Example 10 is that an unmodified conventional polyurethane acrylic resin is used. Comparative Example 8 The difference between this example and Example 10 is that the pigment is directly added without using pigment-loaded foamed alumina particles. According to the above embodiment and in combination with the above preparation method, the ultra-wear-resistant and scratch-resistant UV coating is coated on the treated wooden board, and after UV curing, a coating with a thickness of 25 μm is formed, and conventional performance (substrate adhesion (100 grids), color, coating hardness), wear resistance and Vickers hardness tests are carried out. The conventional properties of the coating are tested using conventional coating testing methods; The Vickers hardness of the coating was tested using a hardness tester, the applied load was 0.0981N, and the hardness value (Hv) was measured; The wear resistance of the coating was tested using a flat abrasion tester. The experimental conditions were: the applied load was 294N, 600# abrasive paper was used, 4800 times of flat grinding, the wear mark was 30mm×12mm, the wear rate was calculated and the color change was observed; Performance parameters are shown in Table 2: Table 2

Claims

1. A super wear-resistant and scratch-resistant UV coating, characterized in that: In parts by weight, it includes the following ingredients: The particle size of the pigment-loaded foamed alumina particles is 10-100 μm, and the porosity of the foamed alumina particles is 80-97%.

2. The ultra-wear-resistant and scratch-resistant UV coating according to claim 1, characterized in that: The preparation method of the modified polyurethane acrylic resin is as follows, in parts by weight: (1) 5 parts of hydroxy-terminated polydimethylsiloxane, 4.5 parts of pentaerythritol triacrylate, 0.1 parts of dibutyltin dilaurate and 0.2 parts of p-hydroxyanisole were mixed, N2 was introduced, and the mixture was stirred uniformly; (2) Raise the temperature to 80°C and begin to dropwise add 100 parts of isophorone diisocyanate for 3-4 hours; (3) Pentaerythritol triacrylate is added to neutralize the unreacted isocyanate groups to obtain modified polyurethane acrylic resin.

3. The ultra-wear-resistant and scratch-resistant UV coating according to claim 1, characterized in that: The active diluent is a complex of HDDA and DPHA, with a ratio of 1:(1-1.5).

4. The ultra-wear-resistant and scratch-resistant UV coating according to claim 1, characterized in that: The photoinitiator is a mixture of benzophenone and hydroxycyclohexyl phenyl ketone, or one or a mixture of several of acylphosphorus oxides.

5. The ultra-wear-resistant and scratch-resistant UV coating according to claim 1, characterized in that: The preparation method of the pigment-loaded foamed alumina particles is as follows: Step 1: soak a polyurethane foam with a pore size of 100 PPI in a 10-20% NaOH solution for 2-3 hours, then soak it in a constant temperature water bath at 60°C for 3 hours, rub it repeatedly to remove the inter-grid membrane, and rinse it with water to obtain the treated polyurethane foam; Step 2: Take 50-80 parts of nano-alumina, 5-8 parts of mesoporous alumina fibers, 3-6 parts of hollow silicon carbide microspheres, 3-5 parts of magnesium oxide, 10-15 parts of silicon powder and 2-5 parts of nano-zirconium oxide, mix and stir evenly to obtain a mixed component, add a 35-50% aluminum dihydrogen phosphate solution to form a slurry, and slurry for 12 hours; Step 3: placing the treated polyurethane foam in the slurry, repeatedly dipping and squeezing, removing the air in the polyurethane foam, and when the slurry is fully immersed in the polyurethane foam and uniformly adsorbed on the polyurethane foam, squeezing the saturated polyurethane foam, squeezing out the excess slurry, and obtaining the green blank; Step 4: After drying the green blank at 80°C, transfer it to a high-temperature box-type resistance furnace for sintering, heat it to 600°C at a heating rate of 0.5°C / min, keep it warm for 2 hours, continue to heat it to 1200°C at a heating rate of 0.3°C / min, keep it warm for 10 hours, and obtain foamed alumina; Step 5: clean the foamed alumina, dry it, crush it and sieve it to obtain foamed alumina particles; Step 6: Take 6 parts of foamed alumina particles, add 100 parts of water, add citric acid to modify, then add 2 parts of organic pigments, and keep the temperature at 70°C for 1-2 hours; Step 7: Add 6 parts of silane coupling agent and 20 parts of 95% ethanol, and react at 70°C for 1-2 hours; Step 8: Add 1.2-1.5 parts of methyl methacrylate, 20 parts of 95% ethanol and ammonium persulfate, and react for 2-3 hours; Step 9: After filtering, dry in the air, wash with 95% ethanol, and dry to obtain the pigment-loaded foamed alumina particles.

6. The ultra-wear-resistant and scratch-resistant UV coating according to claim 5, characterized in that: The particle size of the nano-alumina is 30-100nm, the particle size of the silicon carbide hollow microsphere is 400-580nm, the particle size of the magnesium oxide is 260-500nm, the particle size of the silicon micropowder is 0.5-2μm, and the particle size of the nano-zirconium oxide is 30-80nm.

7. The ultra-wear-resistant and scratch-resistant UV coating according to claim 5, characterized in that: The mesoporous alumina fiber has mesopores of 2-4 nm on its surface and an average specific surface area of ​​322 m 2 / g, fiber diameter is 200-300nm, and length is 7-10μm.

8. The ultra-wear-resistant and scratch-resistant UV coating according to claim 5, characterized in that: The mass of the aluminum dihydrogen phosphate solution is 20-25% of the mixed components.

9. The ultra-wear-resistant and scratch-resistant UV coating according to claim 1, characterized in that: The auxiliary agent is any one of a defoaming agent, a formaldehyde removal additive, and an antibacterial additive, or a combination of two or more thereof.

10. The method for preparing a super wear-resistant and scratch-resistant UV coating according to any one of claims 1 to 9, characterized in that: The following steps are involved: After evenly mixing the modified polyurethane acrylic resin, active diluent, photoinitiator, BYK331 leveling agent and additives, add the pigment-loaded foamed alumina particles and stir evenly again.

Citation Information

Patent Citations

  • Preparation method of foamed ceramic for indoor air purification

    CN106116672A

  • Infrared radiation resistant polyurethane foam material and processing method thereof

    CN109251513A

  • Rapidly-cured UV printing ink and preparation method thereof

    CN118685070A